Nutritional and Antioxidant Value of Horticulturae Products - Guidi, Lucia; De Bellis, Luigi; Pardossi, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
There is a worldwide growing interest toward the nutritional and antioxidant values of fruits and vegetables, especially because phytochemicals in natural products are perceived as necessary for a healthier diet due to their high antioxidant capacity. This book provides readers with novel insights into how quality, in terms of nutritional and antioxidant values, is influenced and/or controlled genetically, environmentally, and by different postharvest treatments. This book is a collection of important pieces of research covering different aspects related to the nutritional and antioxidant values of some horticultural species, including edible flowers, Italian green tea, and stinging nettle, along with potato and sweet potato. Today's food products are all the more appreciated for their content of phytonutriceuticals, and, therefore, horticulture has to turn to the supply of products with a variety of valuable metabolites and aromas. It is the task of researchers to study these compounds and enable the enhancement of horticultural products.